Applying the ‘Write Short’ Concept in a University Degree Assessment Strategy - O'Brien, Justin (Journal of Academic Writing, 2018)
It is a remark credited to several great writers: the admission, ‘I didn’t have time to write you a short letter, so I wrote you this long one instead’. Spilling your guts is easy; being concise takes time. Short is harder; content-rich, succinct writing requires supreme skill and considered application. This short paper argues the case that small is beautiful when we think about setting university assignment word counts.